2015
DOI: 10.1002/hed.23865
|View full text |Cite
|
Sign up to set email alerts
|

Conventional radiotherapy versus concurrent chemoradiotherapy versus accelerated radiotherapy in locoregionally advanced carcinoma of head and neck: Results of a prospective randomized trial

Abstract: CRT is associated with significantly better locoregional control as compared to RT and accelerated RT with higher but acceptable acute and late toxicities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 13 publications
1
42
0
1
Order By: Relevance
“…The control group of a four-arm trial 4 was triplicated (ie, data for patients in the control group were copied twice to have three control arms to compare with each experimental arm), a 2 × 2 trial (EORTC 22962 45 ) included three relevant comparisons for the meta-analysis, and three three-arm trials 36,37,55 included two relevant comparisons. The 33 trials included in the analysis of fractionation schedules (comparison 1) were divided into four predefined subgroups, depending on the type of radiotherapy: hyperfractionation (eight comparisons, including the unpublished EORTC 22962 trial), 4,33,44,45,49,50,56 moderately accelerated radiotherapy (19 comparisons), 2,4,30,32,3439,41,42,46,54,55,5759 very accelerated radiotherapy (seven comparisons, including the unpublished CHARTWEL trial), 3,47,5153,60 and moderately hypofractionated (dose per fraction between 2–2·5 Gy [two comparisons]; 31,40 appendix pp 17–18).…”
Section: Resultsmentioning
confidence: 99%
“…The control group of a four-arm trial 4 was triplicated (ie, data for patients in the control group were copied twice to have three control arms to compare with each experimental arm), a 2 × 2 trial (EORTC 22962 45 ) included three relevant comparisons for the meta-analysis, and three three-arm trials 36,37,55 included two relevant comparisons. The 33 trials included in the analysis of fractionation schedules (comparison 1) were divided into four predefined subgroups, depending on the type of radiotherapy: hyperfractionation (eight comparisons, including the unpublished EORTC 22962 trial), 4,33,44,45,49,50,56 moderately accelerated radiotherapy (19 comparisons), 2,4,30,32,3439,41,42,46,54,55,5759 very accelerated radiotherapy (seven comparisons, including the unpublished CHARTWEL trial), 3,47,5153,60 and moderately hypofractionated (dose per fraction between 2–2·5 Gy [two comparisons]; 31,40 appendix pp 17–18).…”
Section: Resultsmentioning
confidence: 99%
“…Groupe d'Oncologie Radiotherapie Tete et Cou (GORTEC 99-02) [22] was the largest study included in the meta-analysis. Data from a previously reported abstract were extracted initially in brief and subsequently updated through personal communication and a full-text publication [23]. Two other studies [24,25] using a non-inferiority design for comparing CCRT with concomitant boost radiotherapy (CBRT) were also included.…”
Section: Resultsmentioning
confidence: 99%
“…The AFRT schedules that were used in the studies were also heterogeneous. Although one trial used a split-course AFRT schedule [21], two used two different forms of acceleration [22,23] and the remaining two used the CBRT regimen [24,25]. None of the included studies used HFRT as altered fractionation that had shown the maximal benefit among all AFRT schedules in the MARCH metaanalysis [12,13].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations